Potensi semangka (citrullus lanatus) sebagai bahan aktif alami dalam sediaan kosmetik: tinjauan literatur - Al Haqqi, M. Thoriq Farhan (Maliki Interdisciplinary Journal, 2026)
Watermelon (Citrullus lanatus) has potential as a natural active ingredient in topical cosmetic formulations due to its bioactive compound content that supports skin health. This study aimed to review the utilization of different parts of watermelon in cosmetic preparations through a literature review approach. The review included open-access Indonesian scientific articles published between 2019 and 2025 that focused on the use of watermelon fruit or rind in topical cosmetic products. The results indicate that the white rind (mesocarp) is the most frequently utilized part and has been formulated into various dosage forms, including moisturizing gels, clay masks, and moisturizing creams. The commonly evaluated parameters included organoleptic properties, pH, homogeneity, viscosity, spreadability, adhesiveness, physical stability, and moisturizing effectiveness. All reviewed studies reported that watermelon-based cosmetic formulations met acceptable physical quality standards and demonstrated functional benefits, particularly moisturizing and antioxidant activities. Some formulations, such as creams containing specific extract concentrations and combinations of watermelon rind and papaya peel extracts, showed optimal moisturizing effects. Based on these findings, watermelon demonstrates strong potential as a natural active ingredient for the development of topical cosmetic products.